Eco-engineered vertical seawall panels with augmented habitat complexity can create a novel and biodiverse ecosystem in a coastal megacity - Thea E. Bradford; Juan Carlos Astudillo; Charlene Lai; Rainbow W.S. Leung; Jay J. Minuti; Rebecca L. Morris; Stephen J. Hawkins; Janet Kit Yan Chan; Cheryl K.C. Chu; Kenneth Mei Yee Leung (Marine Environmental Research, 2026)

Chemical and isotopic analyses reconstruct multi-scalar copper circulation networks in West Africa: evidence from Akjoujt and Walaldé, 1st millenium BCE – 1st millenium CE - Jay Stephens; Antoine Courcier; Alioune Deme; Thomas Fenn; Susan Keech McIntosh; Roderick J. McIntosh; Guillaume Sarah; Virginie Renson (Archaeological and Anthropological Sciences, 2026)

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Editorial perspective: How to minimize the risk of your manuscript being rejected: Perspectives to get your paper published in ‘Crop Protection’ - Jay Ram Lamichhane; Francis P.F. Reay-Jones; Sheng Qiang; Stephen N. Wegulo (Crop Protection, 2025)

Evaluation of organic products to control blueberry rust - Kara M. Barry; Michele Buntain; Eugene Chau; Melinda Simpson; Stephen Morris; Jay Anderson (Crop Protection, 2025)

Clarifying the role of the resist–accept–direct framework in supporting resource management planning processes - Gregor W. Schuurman; Wylie Carr; Cat Hawkins Hoffman; David J. Lawrence; Brian W. Miller; Erik A. Beever; Jean Brennan; Katherine R. Clifford; Scott Covington; Shelley D. Crausbay; Amanda E. Cravens; John Gross; et al. (Conservation Biology, 2025)

Greening of grey and murky harbours: enhancing biodiversity and ecosystem functioning on artificial shorelines - Thea E. Bradford; Juan Carlos Astudillo; Charlene Lai; Rainbow W.S. Leung; Jay J. Minuti; Stephen Hawkins; Rebecca L. Morris; Janet K.Y. Chan; Kenneth Mei Yee Leung (Marine Pollution Bulletin, 2025)

Turning riprap into reefs: Integrating oyster shells into shoreline armouring - Thea E. Bradford; Chi C. Lo; Juan Carlos Astudillo; Rainbow W.S. Leung; Charlene Lai; Jay J. Minuti; Carmen K.M. Wong; Stephen J. Hawkins; Rebecca L. Morris; Kenneth Mei Yee Leung (Marine Pollution Bulletin, 2025)

Shepherd's beaked whale ( Tasmacetus shepherdi ) produces a diverse variety of ultrasonic pulses - Stephen M. Dawson; Jay Barlow; Marta Guerra; Eva. M. Leunissen; Trudi A. Webster; William J. Rayment (Marine Mammal Science, 2025)

Assessment of laser ablation and solution-based ICP-MS applications commonly used in otolith geochemical analysis of marine teleosts - Michelle Zapp Sluis; Daniel L. Lippi; Phillip J. Sanchez; Nathaniel R. Miller; Shane A. Stephens; Beatrice P. Ferreira; Jay R. Rooker (Frontiers in Marine Science, 2025)
Different applications of inductively coupled plasma mass spectrometry (ICP-MS) have the potential to influence results of otolith geochemical assays. Laser ablation and solution-based ICP-MS were compared on paired otoliths from three species of juvenile fish representative of estuarine (red drum [ Sciaenops ocellatus ]), coastal/reef (gray parrotfish [ Sparisoma axillare ]), and pelagic (blackfin tuna [ Thunnus atlanticus ]) ecosystems. Additionally, two laser ablation techniques (continuous line transects and series of spots) were performed to determine whether these two commonly used approaches yielded comparable results. No significant differences existed between line transects and spots for any of the three species investigated, with high correlations occurring for all otolith element:Ca (E:Ca) values retained for statistical testing (Mg:Ca, Mn:Ca, Sr:Ca, Ba:Ca), suggesting that both laser ablation techniques produced equivalent otolith E:Ca values. In contrast, pronounced differences in E:Ca values were detected between laser ablation (across otolith transverse section) and solution-based (whole otolith dilution) applications on paired sagittal otoliths. While some E:Ca discrepancies varied among the three species, overall otolith E:Ca values were higher when quantified by laser ablation, except for Ba:Ca which tended to be higher when analyzed by solution-based ICP-MS. Differences observed between laser ablation and solution-based applications are the result of the allometric growth of the otolith and may become more pronounced in older, larger individuals as the differential growth along the otolith axes becomes less uniform with age. Further, laser ablation techniques can examine life history profiles and discern fluctuations over time, proving a preferred application over solution-based analysis.

Effects of a large-scale bioretention installation on the species composition of an urban bird community as determined by passive acoustic monitoring - David Wituszynski; Donald Hayford; Angelika Poesel; Gautam Apte; Stephen N. Matthews; Jay Martin (Environmental Monitoring and Assessment, 2024)

Genomic evaluation of mud sunfish in the atlantic slope drainage - Stephen Knott; Richard Raesly; Daniel Hocking; Jay Stauffer; Amy Welsh (Fisheries Research, 2024)

Description and taxonomic assessment of fossil Cercopithecidae from the Pliocene Galili Formation (Ethiopia) - Hailay G. Reda; Stephen R. Frost; Evan A. Simons; Jay Quade; Scott W. Simpson (Journal of Human Evolution, 2024)

Geographic distribution of the Cross Seamount beaked whale based on acoustic detections - Jennifer L. K. McCullough; E. Elizabeth Henderson; Jennifer S. Trickey; Jay Barlow; Simone Baumann‐Pickering; Roanne Manzano‐Roth; Gabriela Alongi; Stephen Martin; Selene Fregosi; David K. Mellinger; Holger Klinck; Angela R. Szesciorka; et al. (Marine Mammal Science, 2024)
Beaked whales produce frequency‐modulated echolocation pulses that appear to be species‐specific, allowing passive acoustic monitoring to play a role in understanding spatio‐temporal patterns. The Cross Seamount beaked whale is known only from its unique echolocation signal (BWC) with no confirmed species identification. This beaked whale spans the Pacific Ocean from the Mariana Archipelago to Baja California, Mexico, south to the equator, but only as far north as latitude 29°N. Within these warm waters, 92% of BWC detections occurred at night, 6% during crepuscular periods, and only 2% during daylight hours. Detections of BWC signals on drifting recorders with a vertical hydrophone array at 150 m depth demonstrated that foraging often occurred shallow in the water column (

Addressing transboundary challenges: Exploring the interactive relations between collaborative governance and transboundary marine spatial planning in Europe - Shenghui Li; Stephen Jay (Marine Policy, 2023)

Estuarine-coastal connectivity and partial migration of southern flounder in the Gulf of Mexico - Christopher Steffen; Shane Stephens; Michael A. Dance; Daniel L. Lippi; Christine C. Jensen; R.J. David Wells; Jay R. Rooker (Estuarine, Coastal and Shelf Science, 2023)

Uranus ring occultation observations: 1977–2006 - Richard G. French; Colleen A. McGhee-French; Mitchell Gordon; Richard L. Baron; Amanda S. Bosh; Marc W. Buie; Nancy Chanover; Mary Ann Clark; Edward W. Dunham; Linda M. French; Ian S. Glass; Jay D. Goguen; et al. (Icarus, 2023)

The genetics of monogenic intestinal epithelial disorders - Stephen J. Babcock; David Flores-Marin; Jay R. Thiagarajah (Human Genetics, 2023)
Monogenic intestinal epithelial disorders, also known as congenital diarrheas and enteropathies (CoDEs), are a group of rare diseases that result from mutations in genes that primarily affect intestinal epithelial cell function. Patients with CoDE disorders generally present with infantile-onset diarrhea and poor growth, and often require intensive fluid and nutritional management. CoDE disorders can be classified into several categories that relate to broad areas of epithelial function, structure, and development. The advent of accessible and low-cost genetic sequencing has accelerated discovery in the field with over 45 different genes now associated with CoDE disorders. Despite this increasing knowledge in the causal genetics of disease, the underlying cellular pathophysiology remains incompletely understood for many disorders. Consequently, clinical management options for CoDE disorders are currently limited and there is an urgent need for new and disorder-specific therapies. In this review, we provide a general overview of CoDE disorders, including a historical perspective of the field and relationship to other monogenic disorders of the intestine. We describe the genetics, clinical presentation, and known pathophysiology for specific disorders. Lastly, we describe the major challenges relating to CoDE disorders, briefly outline key areas that need further study, and provide a perspective on the future genetic and therapeutic landscape.

Metabolic syndrome is associated with aggressive prostate cancer regardless of race - Lourdes Guerrios-Rivera; Lauren E. Howard; Emily K. Wiggins; Cathrine Hoyo; Delores J. Grant; Tyler R. Erickson; Jaruda Ithisuphalap; Alexis R. Freedland; Adriana C. Vidal; Jay H. Fowke; Stephen J. Freedland (Cancer Causes & Control, 2023)

Ambient particulate matter pollution of different sizes associated with recurrent stroke hospitalization in China: A cohort study of 1.07 million stroke patients - Miao Cai; Xiaojun Lin; Xiaojie Wang; Shiyu Zhang; Zhengmin (Min) Qian; Stephen Edward McMillin; Hannah E. Aaron; Hualiang Lin; Jing Wei; Zilong Zhang; Jay Pan (Science of The Total Environment, 2023)

Effects of grid spacing on high-frequency precipitation variance in coupled high-resolution global ocean–atmosphere models - Charles X. Light; Brian K. Arbic; Paige E. Martin; Laurent Brodeau; J. Thomas Farrar; Stephen M. Griffies; Ben P. Kirtman; Lucas C. Laurindo; Dimitris Menemenlis; Andrea Molod; Arin D. Nelson; Ebenezer Nyadjro; et al. (Climate Dynamics, 2022)
High-frequency precipitation variance is calculated in 12 different free-running (non-data-assimilative) coupled high resolution atmosphere–ocean model simulations, an assimilative coupled atmosphere–ocean weather forecast model, and an assimilative reanalysis. The results are compared with results from satellite estimates of precipitation and rain gauge observations. An analysis of irregular sub-daily fluctuations, which was applied by Covey et al. (Geophys Res Lett 45:12514–12522, 2018. https://doi.org/10.1029/2018GL078926 ) to satellite products and low-resolution climate models, is applied here to rain gauges and higher-resolution models. In contrast to lower-resolution climate simulations, which Covey et al. (2018) found to be lacking with respect to variance in irregular sub-daily fluctuations, the highest-resolution simulations examined here display an irregular sub-daily fluctuation variance that lies closer to that found in satellite products. Most of the simulations used here cannot be analyzed via the Covey et al. (2018) technique, because they do not output precipitation at sub-daily intervals. Thus the remainder of the paper focuses on frequency power spectral density of precipitation and on cumulative distribution functions over time scales (2–100 days) that are still relatively “high-frequency” in the context of climate modeling. Refined atmospheric or oceanic model grid spacing is generally found to increase high-frequency precipitation variance in simulations, approaching the values derived from observations. Mesoscale-eddy-rich ocean simulations significantly increase precipitation variance only when the atmosphere grid spacing is sufficiently fine (< 0.5°). Despite the improvements noted above, all of the simulations examined here suffer from the “drizzle effect”, in which precipitation is not temporally intermittent to the extent found in observations.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Modeling ammonia volatilization from urea application to agricultural soils in the DayCent model - Ram B. Gurung; Stephen M. Ogle; F. Jay Breidt; Stephen Williams; Yao Zhang; Stephen J. Del Grosso; William J. Parton; Keith Paustian (Nutrient Cycling in Agroecosystems, 2021)

Monocyte counts and prostate cancer outcomes in white and black men: results from the SEARCH database - Azeb Yirga; Taofik Oyekunle; Lauren E. Howard; Amanda M. De Hoedt; Matthew R. Cooperberg; Christopher J. Kane; William J. Aronson; Martha K. Terris; Christopher L. Amling; Emanuela Taioli; Jay H. Fowke; Zachary Klaanssen; et al. (Cancer Causes & Control, 2021)

Neutrophil, lymphocyte and platelet counts, and risk of prostate cancer outcomes in white and black men: results from the SEARCH database - Adriana C. Vidal; Lauren E. Howard; Amanda de Hoedt; Matthew R. Cooperberg; Christopher J. Kane; William J. Aronson; Martha K. Terris; Christopher L. Amling; Emanuela Taioli; Jay H. Fowke; Stephen J. Freedland (Cancer Causes & Control, 2018)

A constrained least-squares approach to combine bottom-up and top-down CO2 flux estimates - Daniel Cooley; F. Jay Breidt; Stephen M. Ogle; Andrew E. Schuh; Thomas Lauvaux (Environmental and Ecological Statistics, 2013)

Shallow seismicity, triggered seismicity, and ambient noise tomography at the long-dormant Uturuncu Volcano, Bolivia - Jennifer A. Jay; Matthew E. Pritchard; Michael E. West; Douglas Christensen; Matthew Haney; Estela Minaya; Mayel Sunagua; Stephen R. McNutt; Mario Zabala (Bulletin of Volcanology, 2012)

Downscaling and visioning of mountain snow packs and other climate change implications in North Vancouver, British Columbia - Stewart Jay Cohen; Stephen Sheppard; Alison Shaw; David Flanders; Sarah Burch; Bill Taylor; David Hutchinson; Alex Cannon; Stuart Hamilton; Brent Burton; Jeff Carmichael (Mitigation and Adaptation Strategies for Global Change, 2012)

New genetic lineages, host associations and circulation pathways of Neorickettsia endosymbionts of digeneans - Vasyl Tkach; Jay Schroeder; Stephen Greiman; Jefferson Vaughan (Acta Parasitologica, 2012)
Neorickettsia is a genus of intracellular bacteria endosymbiotic in digeneans that may also invade cells of vertebrates and are known to cause diseases of wildlife and humans. Herein, we report results of screening for Neorickettsia of an extensive collection of DNA extracts from adult and larval digeneans obtained from various vertebrates and mollusks in the United States. Seven isolates of Neorickettsia were detected by PCR and sequenced targeting a 527 bp long region of 16S rRNA. Sequence comparison and phylogenetic analysis demonstrated that four isolates matched published sequences of Neorickettsia risticii. Three other isolates, provisionally named “catfish agents 1 and 2” (obtained from Megalogonia ictaluri and Phyllodistomum lacustri, both parasitic in catfishes) and Neorickettsia sp. (obtained from cercariae of Diplostomum sp.), differed from previously known genotypes of Neorickettsia and are likely candidates for new species. All 7 isolates of Neorickettsia were obtained from digenean species and genera that were not previously reported as hosts of these bacteria. Members of four digenean families (Dicrocoeliidae, Heronimidae, Macroderoididae and Gorgoderidae) are reported as hosts of Neorickettsia for the first time. Our study reveals several new pathways of Neorickettsia circulation in nature. We have found for the first time a Neorickettsia from a digenean (dicrocoeliid Conspicuum icteridorum) with an entirely terrestrial life cycle. We found N. risticii in digeneans (Alloglossidium corti and Heronimus mollis) with entirely aquatic life cycles. Previously, this Neorickettsia species was known only from digeneans with aquatic/terrestrial life cycles. Our results suggest that our current knowledge of the diversity, host associations and circulation of neorickettsiae is far from satisfactory.

Nitrogen transformations in a through‐flow wetland revealed using whole‐ecosystem pulsed 15 N additions - Jonathan M. O'Brien; Stephen K. Hamilton; Lauren E. Kinsman-Costello; Jay T. Lennon; Nathaniel E. Ostrom (Limnology and Oceanography, 2012)
We used pulsed and continuous additions of 15 N together with whole‐ecosystem metabolism measurements to elucidate the mechanisms of nitrogen (N) transformations in a small (1170 m 2 ) through‐flow wetland situated along a stream. From measurements of the wetland inflow and outflow, we observed a consistent decrease in nitrate (by 10% of inflow concentrations), while ammonium increased by an order of magnitude. Outflow ammonium concentrations oscillated in a diel cycle, inverse to the concentration of dissolved oxygen (i.e., greater ammonium export at night). The pulsed 15 N additions showed little uptake of nitrate over time in the wetland and rapid daytime uptake of ammonium from the water column (rate constant, k t = 0.11 h −1 ). A steady‐state 15 N‐ammonium addition demonstrated a similar rate of ammonium uptake (k t = 0.067 h −1 ), no detectable nitrification, and highlighted the spatial pattern of ammonium and nitrate uptake within the wetland. Porewater concentration profiles suggest high rates of net ammonium diffusion from the sediments. Ecosystem metabolism measurements indicate that release was attenuated during the day by autotrophic uptake, resulting in lower ammonium export during the day. Denitrification rates were modeled from dissolved N 2 : Ar ratios, but they were not sufficient to account for the observed loss in nitrate. Nitrate was removed near the pond inflow but not actively cycled throughout the pond, while the balance between sediment release and subsequent uptake of ammonium from the water‐column dominated N cycling in this wetland.

Evolution of a Carboniferous carbonate-hosted sphalerite breccia deposit, Isle of Man - Kevin L. Shelton; Justin M. Beasley; Jay M. Gregg; Martin S. Appold; Stephen F. Crowley; James P. Hendry; Ian D. Somerville (Mineralium Deposita, 2011)

Forest Policy / Biosecurity - Linda Heath; Clark Row; Robert Perschel; Douglas Boucher; Patricia Elias; Katherine Lininger; Calen May-Tobin; Earl Saxon; Steven Ruddell; Sally Collins; Sarah Ruddell; Mo Zhou; et al. (Journal of Forestry, 2011)
7Massive fires in Indonesian peatlands in the 1990s and in eastern Russian peatlands in 2002 and last year have highlighted the need to manage forests overlying peat deposits, as well as converted peat forests and open peatlands. Peat or peaty soils, contain 65% or more of partially decayed vegetation, can burn freely or underground. They cover some 10 percent of worldwide forests and contain 25 percent of all terrestrial carbon. Recent massive greenhouse gas (GHG) emissions from fires in forested peat and peatland in Indonesia and in Russia highlight the need for policies to reduce GHG emissions. We discuss major peatland areas and quantify their carbon stocks and potential GHG emissions. Trends show that year-to-year emissions are variable, with huge pulses that are a significant share of global GHG emissions. We group suggested policy options into three approaches. The first approach, which will reduce peat-related product demand, includes a) restricting peat, and products produced on cleared forested peatland, from being labeled or counted in GHG reduction achievements, as renewable (which palm oil currently is considered); b) developing full substitutes for horticultural peat (comprising about half mined peat use); and c) developing renewable power in countries still dependent on peat for power generation. These options reduce the rate of developing newly mined peat/forest areas. Options for a second approach, which treat already drained and cleared forested peatlands, are: d) restoring functioning peat ecosystems by closing drainage ditches, allowing natural rewetting, and “seeding” with peat vegetation fragments, e) requiring current peat operators to restore mined areas right after all peat is removed, and f) converting them to other land uses, despite the acidic conditions of mined peat bogs. These options sharply reduce risks of peat fires. Finally, a third group of policy options reduces ignition risks and limit fire spread: g) developing monitoring, suppression techniques, h) organizing local landowner protection groups and i) improving public fire organizations.

An examination of male and female odds ratios by BMI, cigarette smoking, and alcohol consumption for cancers of the oral cavity, pharynx, and larynx in pooled data from 15 case–control studies - Jay H. Lubin; Joshua Muscat; Mia M. Gaudet; Andrew F. Olshan; Maria Paula Curado; Luigino Dal Maso; Victor Wünsch-Filho; Erich M. Sturgis; Neonilia Szeszenia-Dabrowska; Xavier Castellsague; Zuo-Feng Zhang; Elaine Smith; et al. (Cancer Causes & Control, 2011)

Electrotactile stimuli delivered across fingertips inducing the Cutaneous Rabbit Effect - Jay P. Warren; Marco Santello; Stephen I. Helms Tillery (Experimental Brain Research, 2010)

Heat balance and cumulative heat storage during exercise performed in the heat in physically active younger and middle-aged men - Glen P. Kenny; Daniel Gagnon; Lucy E. Dorman; Stephen G. Hardcastle; Ollie Jay (European Journal of Applied Physiology, 2010)

Basal Ganglia MR Relaxometry in Obsessive-Compulsive Disorder: T2 Depends Upon Age of Symptom Onset - Stephen Correia; Emily Hubbard; Jason Hassenstab; Agustin Yip; Josef Vymazal; Vit Herynek; Jay Giedd; Dennis L. Murphy; Benjamin D. Greenberg (Brain Imaging and Behavior, 2010)

Scale and uncertainty in modeled soil organic carbon stock changes for US croplands using a process‐based model - STEPHEN M. OGLE; F. JAY BREIDT; MARK EASTER; STEVE WILLIAMS; KENDRICK KILLIAN; KEITH PAUSTIAN (Global Change Biology, 2010)
Process‐based model analyses are often used to estimate changes in soil organic carbon (SOC), particularly at regional to continental scales. However, uncertainties are rarely evaluated, and so it is difficult to determine how much confidence can be placed in the results. Our objective was to quantify uncertainties across multiple scales in a process‐based model analysis, and provide 95% confidence intervals for the estimates. Specifically, we used the Century ecosystem model to estimate changes in SOC stocks for US croplands during the 1990s, addressing uncertainties in model inputs, structure and scaling of results from point locations to regions and the entire country. Overall, SOC stocks increased in US croplands by 14.6 Tg C yr −1 from 1990 to 1995 and 17.5 Tg C yr −1 during 1995 to 2000, and uncertainties were ±22% and ±16% for the two time periods, respectively. Uncertainties were inversely related to spatial scale, with median uncertainties at the regional scale estimated at ±118% and ±114% during the early and latter part of 1990s, and even higher at the site scale with estimates at ±739% and ±674% for the time periods, respectively. This relationship appeared to be driven by the amount of the SOC stock change; changes in stocks that exceeded 200 Gg C yr −1 represented a threshold where uncertainties were always lower than ±100%. Consequently, the amount of uncertainty in estimates derived from process‐based models will partly depend on the level of SOC accumulation or loss. In general, the majority of uncertainty was associated with model structure in this application, and so attaining higher levels of precision in the estimates will largely depend on improving the model algorithms and parameterization, as well as increasing the number of measurement sites used to evaluate the structural uncertainty.

Assessing the Sensitivity of Quantitative Structural Activity Analysis Models for Evaluating New Military Compounds - Jay Clausen; Randall Cramer; Stephen Clough; Michael Gray; Patrick Gwinn (Water, Air, & Soil Pollution, 2009)

Core temperature differences between males and females during intermittent exercise: physical considerations - Daniel Gagnon; Lucy E. Dorman; Ollie Jay; Stephen Hardcastle; Glen P. Kenny (European Journal of Applied Physiology, 2009)

Interactions Among Wildland Fires in a Long-Established Sierra Nevada Natural Fire Area - Brandon M. Collins; Jay D. Miller; Andrea E. Thode; Maggi Kelly; Jan W. van Wagtendonk; Scott L. Stephens (Ecosystems, 2009)

A Meta‐Analysis of Bird Responses to Uniform Partial Harvesting across North America - MARK C. VANDERWEL; JAY R. MALCOLM; STEPHEN C. MILLS (Conservation Biology, 2007)
Most data on the effects of partial‐harvest silviculture (where live trees are purposely retained at the time of harvest) on birds come from one or a few discrete harvesting treatments. It is thus difficult to infer species responses across a continuous gradient of tree retention from individual studies. To quantify the levels of tree retention expected to produce specified changes in the relative abundance of individual species, we carried out a meta‐analysis of 42 studies that examined the impacts of uniform partial harvesting on North American birds. Of 34 species, sigmoidal models showed a negative effect of harvesting for 14 species and a positive effect for 6 species. Ovenbirds ( Seiurus aurocapilla ) and Brown Creepers ( Certhia americana ) were the species most sensitive to harvesting. Most of the 14 species that were negatively affected by harvesting showed 25%, 50%, and 75% reductions in abundance (relative to control sites) at tree retention levels ranging from 45 to 85%, 30–70%, and 15–50%, respectively. A few species, such as Yellow‐rumped Warblers ( Dendroica coronata ), exhibited these levels of response at lower tree retention or were not predicted to decrease by 75% in harvested stands. Five of the 6 species that were positively affected by harvesting showed at least a 50% increase in abundance at nearly all levels of tree retention, although other early successional bird species did not appear to benefit from the relatively small openings created by uniform partial harvesting. Three of 20 species exhibited stronger responses to harvesting at a given level of tree retention in boreal and northern mixed forests of North America than other regions of the continent, but, with these exceptions, lack of variation among forest regions supported the broad‐scale generality of species' responses to harvesting. The species response models we developed represent useful tools for evaluating stand‐level impacts of partial harvesting on birds within an adaptive management framework. Uniform partial harvesting at light and, to a lesser degree, moderate intensities may be effective approaches to managing habitat for late successional bird species as part of broader ecosystem‐based forest management.

Bias and variance in model results associated with spatial scaling of measurements for parameterization in regional assessments - STEPHEN M. OGLE; F. JAY BREIDT; KEITH PAUSTIAN (Global Change Biology, 2006)
Models are central to global change analyses, but they are often parameterized using data that represent only a portion of heterogeneity in a region. This creates uncertainty in the results and constrains the reliability of model inferences. Our objective was to evaluate the uncertainty associated with differential scaling of parameterization data to model soil organic carbon stock changes as a function of US agricultural land use and management. Specifically, we compared analyses in which model parameters were derived from field experimental data that were scaled to the entire US vs. the same data scaled to climate regions within the country. We evaluated the effect of differential scaling on both bias and variance in model results. Model results had less variance by scaling data to the entire country because of a larger sample size for deriving individual parameter values, although there was a relatively large bias associated with this parameterization, estimated at 2.7 Tg C yr −1 . Even with the large bias, resulting confidence intervals from the two parameterizations had considerable overlap for the estimated national rate of SOC change (i.e. 77% overlap in those intervals). Consequently, the results were relatively similar when focusing on the uncertainty rather than solely on the mean estimate. In contrast, large biases created less overlap in confidence intervals for the change rates within individual climate regions, compared with the national estimates. For example, the overlap in resulting intervals from the two parameterizations was only 32% for the warm temperate moist region, with a corresponding bias of 3.1 Tg C yr −1 . These findings demonstrate that there is a greater risk of making erroneous inferences because of large biases if models are parameterized with broader scale information, such as an entire country, and then used to address impacts at a finer spatial scale, such as sub‐regions within a country. In addition, the study demonstrates a trade‐off between variance and bias in model results that depends on the scaling of data for model parameterization.

Shoreline tufa and tufaglomerate from Pleistocene Lake Bonneville, Utah, USA: stable isotopic and mineralogical records of lake conditions, processes, and climate - Stephen T. Nelson; M. Jay Wood; Alan L. Mayo; David G. Tingey; Dennis Eggett (Journal of Quaternary Science, 2005)
Shoreline carbonate deposits of Pleistocene Lake Bonneville record the conditions and processes within the lake, including the evaporative balance as well as vertical and lateral chemical and isotopic gradients. Tufas (swash‐zone) and tufaglomerates (cemented, subaqueous colluvium or beachrock) on multiple, well‐developed shorelines near the Silver Island Range, Utah, also present an opportunity to examine physicochemical lake processes through time. Three shorelines are represented by carbonate deposits, including the 23–20 ka Stansbury stage, 15–14.5 ka Bonneville stage, and 14.5–14 ka Provo stage. Mean δ 18 O VSMOW values of all three shorelines are statistically indistinguishable ( ∼ 27 ± 1‰), when a few Bonneville samples of unusual composition are neglected. However, differences in primary carbonate mineralogy indicate that the correspondence is an artefact of the different fractionation factors between calcite or aragonite and water. Second, in order to sustain a much smaller, shallower lake during the colder Stansbury stage, the climate must have also been relatively dry. Third, δ 18 O values in tufa are higher than tufaglomerate by ∼ 0.5‰, consistent with greater evaporative enrichment of lake water in the swash zone. Fourth, mean δ 13 C values for the Provo, Stansbury and Bonneville shorelines (4.4, 5.0 and 5.2‰, respectively) show that carbon species were dominated by atmospheric exchange, with the variations produced by differences in the oxidation of organic matter. Comparisons of shoreline carbonates with deep‐lake marls of the same approximate age indicate that shoreline carbonate was much higher in δ 13 C and δ 18 O values (both ∼ 2.5‰) during Bonneville time, whereas isotopic differences were minor (both ∼ 1‰) in Stansbury time. In particular, the Bonneville stage may have sustained large vertical or lateral isotopic gradients due to evaporative enrichment effects on δ 18 O values. In contrast, the lake during the much shallower Stansbury stage may have been well mixed. Differences in the primary mineralogy (Stansbury and Bonneville, aragonite > calcite; Provo, calcite > aragonite) reflect profound differences in lake chemistry in terms of open versus closed‐basin lakes. The establishment of a continuous outlet during Provo time probably reduced the Mg 2+ /Ca 2+ ratio of lake water. Curiously, regardless of primary mineralogy, tufaglomerate cements are enriched in Na + and Cl − and depleted in Mg 2+ relative to capping tufa of the same age. This probably reflects vital or kinetic effects in the swash zone (tufa). We suspect that ‘abiotic’ effects may have been important in the dark pore space of developing tufaglomerate, where the absence of light suppressed photosynthesis. Copyright © 2005 John Wiley & Sons, Ltd.

The potential to mitigate global warming with no‐tillage management is only realized when practised in the long term - Johan Six; Stephen M. Ogle; F. Jay breidt; Rich T. Conant; Arvin R. Mosier; Keith Paustian (Global Change Biology, 2004)
No‐tillage (NT) management has been promoted as a practice capable of offsetting greenhouse gas (GHG) emissions because of its ability to sequester carbon in soils. However, true mitigation is only possible if the overall impact of NT adoption reduces the net global warming potential (GWP) determined by fluxes of the three major biogenic GHGs (i.e. CO 2 , N 2 O, and CH 4 ). We compiled all available data of soil‐derived GHG emission comparisons between conventional tilled (CT) and NT systems for humid and dry temperate climates. Newly converted NT systems increase GWP relative to CT practices, in both humid and dry climate regimes, and longer‐term adoption (>10 years) only significantly reduces GWP in humid climates. Mean cumulative GWP over a 20‐year period is also reduced under continuous NT in dry areas, but with a high degree of uncertainty. Emissions of N 2 O drive much of the trend in net GWP, suggesting improved nitrogen management is essential to realize the full benefit from carbon storage in the soil for purposes of global warming mitigation. Our results indicate a strong time dependency in the GHG mitigation potential of NT agriculture, demonstrating that GHG mitigation by adoption of NT is much more variable and complex than previously considered, and policy plans to reduce global warming through this land management practice need further scrutiny to ensure success.

Uncertainty in estimating land use and management impacts on soil organic carbon storage for US agricultural lands between 1982 and 1997 - Stephen M. Ogle; F. Jay Breidt; Marlen D. Eve; Keith Paustian (Global Change Biology, 2003)
Uncertainty was quantified for an inventory estimating change in soil organic carbon (SOC) storage resulting from modifications in land use and management across US agricultural lands between 1982 and 1997. This inventory was conducted using a modified version of a carbon (C) accounting method developed by the Intergovernmental Panel on Climate Change (IPCC). Probability density functions (PDFs) were derived for each input to the IPCC model, including reference SOC stocks, land use/management activity data, and management factors. Change in C storage was estimated using a Monte‐Carlo approach with 50 000 iterations, by randomly selecting values from the PDFs after accounting for dependencies in the model inputs. Over the inventory period, mineral soils had a net gain of 10.8 Tg C yr −1 , with a 95% confidence interval ranging from 6.5 to 15.3 Tg C yr −1 . Most of this gain was due to setting‐aside lands in the Conservation Reserve Program. In contrast, managed organic soils lost 9.4 Tg C yr −1 , with a 95% confidence interval ranging from 6.4 to 13.3 Tg C yr −1 . Combining these gains and losses in SOC, US agricultural soils accrued 1.3 Tg C yr −1 due to land use and management change, with a 95% confidence interval ranging from a loss of 4.4 Tg C yr −1 to a gain of 6.9 Tg C yr −1 . Most of the uncertainty was attributed to management factors for tillage, land use change between cultivated and uncultivated conditions, and C loss rates from managed organic soils. Based on the uncertainty, we are not able to conclude with 95% confidence that change in US agricultural land use and management between 1982 and 1997 created a net C sink for atmospheric CO 2 .

DMT1: A mammalian transporter for multiple metals - Michael D. Garrick; Kevin G. Dolan; Craig Horbinski; Andrew J. Ghio; Dennis Higgins; Michael Porubcin; Elizabeth G. Moore; Lucille N. Hainsworth; Jay N. Umbreit; Marcel E. Conrad; Lee Feng; Agnieska Lis; et al. (BioMetals, 2003)

Hypotension following mild bouts of resistance exercise and submaximal dynamic exercise - Jay R. MacDonald; J. Duncan MacDougall; Stephen A. Interisano; Kelly M. Smith; Neil McCartney; John S. Moroz; Ed V. Younglai; Mark A. Tarnopolsky (European Journal of Applied Physiology, 1999)

SOUNDS RECORDED FROM BAIRD'S BEAKED WHALE, BERARDIUS BAIRDIL - Stephen Dawson; Jay Barlow; Don Ljungblad (Marine Mammal Science, 1998)

Oxidative stress in silicosis: Evidence for the enhanced clearance of free radicals from whole lungs - Val Vallyathan; Stephen Leonard; Periannan Kuppusamy; Donna Pack; Michael Chzhan; Sherry P. Sanders; Jay L. Zweir (Molecular and Cellular Biochemistry, 1997)